2021
DOI: 10.1155/2021/3301402
|View full text |Cite
|
Sign up to set email alerts
|

PTPRT Could Be a Treatment Predictive and Prognostic Biomarker for Breast Cancer

Abstract: The role of PTPRT in breast cancer was not comprehensively explored and well analyzed. Our study comprehensively searched available databases to analyze the clinical role of PTPRT in breast cancer. We found PTPRT was an antioncogene and could be used to distinguish different stages, age groups, molecular types, and grades for breast cancer. PTPRT might be primary resistance biomarkers for taxane, anthracycline, and ixabepilone but not be acquired resistance biomarkers. Higher PTPRT expression levels were assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 31 publications
(48 reference statements)
0
11
0
Order By: Relevance
“…This exploration revealed six miRNA: mRNA pairs when a higher expression of the miRNAs with positive coefficients intersected with downregulated genes in the high-risk group. Intriguingly, among these downregulated genes, CLEC10A and PTPRT have been demonstrated as poor prognostic factors when their expressions were reduced in breast cancer, suggesting a plausible negative regulatory mechanism of these miRNAs in our TRM signature [92,93]. Similarly, it reduced the expression of the TP63; a known suppressor of cell migration and metastasis and could lead to enhanced tumor invasion and migration [94].…”
Section: Discussionmentioning
confidence: 83%
“…This exploration revealed six miRNA: mRNA pairs when a higher expression of the miRNAs with positive coefficients intersected with downregulated genes in the high-risk group. Intriguingly, among these downregulated genes, CLEC10A and PTPRT have been demonstrated as poor prognostic factors when their expressions were reduced in breast cancer, suggesting a plausible negative regulatory mechanism of these miRNAs in our TRM signature [92,93]. Similarly, it reduced the expression of the TP63; a known suppressor of cell migration and metastasis and could lead to enhanced tumor invasion and migration [94].…”
Section: Discussionmentioning
confidence: 83%
“…As shown in Figure 2(c) , a total of 17 cancer types had significantly downregulated PTPRT levels in cancer tissues compared to normal tissue in most cancer types (the expression of PTPRT in 12/17 cancer types was downregulated, Figure 2(c) ). In addition, some studies reported that the downregulation of PTPRT expression is associated with poor prognosis [ 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…PTPR, a subfamily of class I PTPs, are involved in protein dephosphorylation, which has been shown to inhibit multiple cellular signaling pathways. Previous studies have demonstrated that PTPRD exerts a suppressive effect in breast cancer and liver cancer ( 27 , 28 ). Hsu et al.…”
Section: Discussionmentioning
confidence: 99%
“…PTPR, a subfamily of class I PTPs, are involved in protein dephosphorylation, which has been shown to inhibit multiple cellular signaling pathways. Previous studies have demonstrated that PTPRD exerts a suppressive effect in breast cancer and liver cancer (27,28). Hsu et al demonstrated that deleterious PTPRT/ PTPRD alterations are associated with the shorter progressionfree survival of CRC patients who had received bevacizumab (29).…”
Section: Discussionmentioning
confidence: 99%